ChemInform Abstract: Highly Enantioselective Simmons—Smith Fluorocyclopropanation of Allylic Alcohols via the Halogen Scrambling Strategy of Zinc Carbenoids. Issue 44 (14th October 2013) - Beaulieu, Louis‐Philippe B.; Schneider, Jakob F.; Charette, Andre B.
Abstract Excellent diastereoselectivities are achieved, except for the Z‐cinnamyl alcohol (IV) which gives the trans‐diastereomer (V) only with 4:1 d.r.